EVALUATION OF SOLUTION EFFICIENCY IN MODERNIZATION PROJECT OF LOGISTIC CHAINS - Рославцев, Дмитро Миколайович (Eastern-European Journal of Enterprise Technologies, 2010)
The application features, disadvantages and advantages using methodology of the design analysis, mathematical modeling of logistical circuit work at estimation of introduction efficiency of modernization projects are determined.